2010
DOI: 10.1080/02664760802571333
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of the origin-shifted exponential distribution for control chart construction

Abstract: This study demonstrates that a location parameter of an exponential distribution significantly influences normalization of the exponential. The Kullback-Leibler information number is shown to be an appropriate index for measuring data normality using a location parameter. Control charts based on probability limits and transformation are compared for known and estimated location parameters. The probabilities of type II error (β-risks) and average run length (ARL) without a location parameter indicate an ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…compare some of these charts including the cumulative sum and exponentially‐weighted moving average charts. Some authors suggest applying the regular Shewhart charts after a transformation of the data . Jones and Champ emphasize the early stage process improvement activities when failures occur according a homogeneous Poisson process .…”
Section: Introductionmentioning
confidence: 99%
“…compare some of these charts including the cumulative sum and exponentially‐weighted moving average charts. Some authors suggest applying the regular Shewhart charts after a transformation of the data . Jones and Champ emphasize the early stage process improvement activities when failures occur according a homogeneous Poisson process .…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Abebe [20] compared multiple exponential populations with more than one control. Kao [10] showed that the amount of current needed to break an insulator of the P-type high-voltage metal oxide semiconductor (MOS) transistor (HPM) on a non-volatile drive memory wafer follows the two-parameter exponential distribution and this article nicely demonstrates the importance of the two-parameter exponential distribution in the engineering sciences. In the same year, Wu [27] proposed an interval estimation technique for the scale parameter of a two-parameter exponential distribution based on Type-II progressive censoring.…”
Section: Introductionmentioning
confidence: 83%
“…For example, in the engineering sciences it is used to model the lifespan of electronic components, transmission, engine and mechanical equipment. Nevertheless, many researchers, including Huang, Mukherjee and Yang [8], Kao [10], Krishnamoorthy and Xia [11], Roy and Mathew [17], and Wu [27], have found that in various practical applications, such as measuring the reliability of a product, monitoring the high-voltage of current in certain metal oxide semiconductor transistor on a flash memory wafer, modelling the consumer lifetime, among others, the two-parameter (shifted) exponential distribution should be preferred to the one-parameter exponential distribution. The probability density function (pdf) of the two-parameter exponential distribution is f (x; θ, λ) = 1 λ exp −(x−θ)/λ ; x > θ > 0, λ > 0.…”
Section: Introductionmentioning
confidence: 99%
“…One may see, among others, Wright et al, 1 Mitra and Patankar, 2 Baker et al, 3 Perry and Pignatiello, 4 Baklizi, 5 Doostparast and Balakrishnan, 6 Han et al, 7 Ganguly et al, 8 Cheng et al, 9 and Krishnamoorthy and Xia 10 . Kao 11 emphasized the importance of monitoring‐shifted exponential processes in the context of monitoring high voltage of current in a typical semiconductor transistor on a flash memory wafer. He also illustrated its use in health care monitoring.…”
Section: Introductionmentioning
confidence: 99%